Dual Nanoislands on Ni/C Hybrid Nanosheet Activate Superior Hydrazine Oxidation‐Assisted High‐Efficiency H2 Production. Issue 2 (25th November 2021) - Zhu, Yin; Zhang, Jihua; Qian, Qizhu; Li, Yapeng; Li, Ziyun; Liu, Yi; Xiao, Chong; Zhang, Genqiang; Xie, Yi
Abstract: Clean hydrogen evolution through electrochemical water splitting underpins various innovative approaches to the pursuit of sustainable energy conversion technologies, but it is blocked by the sluggish anodic oxygen evolution reaction (OER). The hydrazine oxidation reaction (HzOR) has been considered as one of the most promising substitute for OER to improve the efficiency of hydrogen evolution reaction (HER). Herein, we construct novel dual nanoislands on Ni/C hybrid nanosheet array: one kind of island represents the part of bare Ni particle surface, while the other stands for the part of core–shell Ni@C structure (denoted as Ni‐C HNSA), in which exposed Ni atoms and Ni‐decorated carbon shell perform as active sites for HzOR and HER respectively. As a result, when the current density reaches 10 mA cm −2, the working potentials are merely −37 mV for HER and ‐20 mV for HzOR. A two‐electrode electrolyzer exhibits superb activity that only requires an ultrasmall cell voltage of 0.14 V to achieve 50 mA cm −2 . Abstract : A Ni/C hybrid nanosheet array with dual‐active nanoisland sites is reported. One type of island represents the bare Ni particle surface, the other consists of core–shell Ni@C structures (denoted as Ni‐C HNSA). The catalyst achieves efficient hydrogen production in an overall hydrazine splitting, showing its potential for practical applications.